Assessing the drinking water quality in the Inner Mongolia Autonomous Region from 2014 to 2018. (24th March 2022) - Wang, X.; Xu, X. Q.; Gao, C. H.; Li, L. H.; Liu, Y.; Zhang, N.; Xia, Y.; Fang, X.; Zhang, X. G.
Abstract: The objective of this study was to understand the drinking water quality state in the Inner Mongolia Autonomous Region from 2014 to 2018 and to derive information that will provide a basis for improving the drinking water quality in the region. Monitoring data for drinking water from the Inner Mongolia Autonomous Region for 2014 to 2018 were analyzed and the results were compared with GB 5749-2006, the Standard Test Method for Drinking Water, and GB 5749-2006, the Drinking Water Quality Standards. Data for a total of 30, 613 water samples were assessed. Of the data for the microbiological index, sensory trait and general chemical index, and toxicological index, 89, 80, and 69% were qualified, respectively. For the toxicological index, the fluoride and nitrate nitrogen data were the least compliant. The water quality in all the cities was generally very suitable for drinking. However, there were marked differences in the qualified rates of drinking water in different areas and the qualified rates of the data for the three indexes were lower in rural areas than in urban areas. Given the varied issues with the drinking water quality, the relevant departments of League cities should implement appropriate and effective treatment measures to improve the drinking water quality and ensure it is safe for residents. HIGHLIGHTS: The values of the microbial, sensory trait and general chemical, and toxicological indexes for drinking water in the Inner Mongolia Autonomous Region have increased over the period from 2014 to 2018. The compliance of the three indexes for drinking water from various sources and cities were different, which required appropriate measures to improve. The quality of drinking water is lower in rural areas than in urban areas. Graphical Abstract